Interpersonal Communication Context and Connection - Altman, Hilary; Clancy, Kristine; Coleman, Elizabeth; Encarnacion, Liz; Khanna, Anu; Kicenski, Karyl; Leonard, Victoria; Mata, Alex; Moran, Rebeca; Plump, Brielle; Reitzel, Armeda; Ruggeri-DiLello, Tiffany; et al. (Open textbook library., 2023)
Interpersonal Communication: Context and Connection provides an engaging overview of interpersonal communication grounded in theory, research, and practical application, with an eye to the lived experience of college students. The first three chapters provide the foundation of interpersonal communication with an examination of the theoretical and conceptual background of communication, self, and perception. The next section of the book examines unique features of messaging, with an exploration of listening, verbal, and nonverbal communication. Chapters 7, 8, and 9 explore dynamic factors that shape interpersonal relationships, including emotions, climate, and conflict. The final chapters of the book delve into communication in context through building and maintaining relationships, the dark side of communication, and workplace relationships.